Multiple Successful Angioembolizations for Refractory Cardiac Failure in a Preterm with Rapidly Involuting Congenital Hemangioma - Sur, Amitava; Manraj, Heran; Lavoie, Pascal M.; Lim, Ken; Courtemanche, Douglas; Brooks, Paul; Albersheim, Susan (American Journal of Perinatology Reports, 2016)
Rapidly involuting congenital hemangiomas (RICH) are the commonest variety of congenital hemangioma, often diagnosed antenatally as high-flow arteriovenous shunts causing hemodynamic compromise to the fetus. The postnatal management of such patients is often challenging. We present the case of an infant boy who was delivered prematurely at 29 weeks of gestation due to fetal compromise by a RICH, with features of high-output cardiac failure and major systemic hemodynamic steal from peripheral organs. Two early angioembolizations were required to manage his high-output cardiac failure. To our knowledge, this infant is the smallest and earliest newborn case of successful angioembolization for a complex, life-threatening vascular anomaly. We discuss the interventional dilemmas regarding the optimal timing of delivery and early embolization.
Keywords: RICH; high-output cardiac failure; angioembolization; preterm